Comparison of the analgesic effect of dezocine and esketamine in combination with sufentanil respectively after laparoscopic cholecystectomy: a prospective randomized controlled study - Boran Deng; Dingding Wang; Zifeng Xie; Yongqin Wang; Li Huang; Manlin Jiang; Tu Shen (BMC Anesthesiology, 2024)
Abstract Background Sufentanil in combination with dezocine or esketamine is often used for postoperative analgesia. However, there is a lack of clinical evidence of efficacy. This study compares the analgesic effects of esketamine and dezocine combined with sufentanil for relieving pain after laparoscopic cholecystectomy(LC). Methods A total of 58 patients were randomly assigned to the esketamine group (ES group) and dezocine group (DE group). In the ES group, 1.5 mg/kg esketamine was used. In the DE group, 0.3 mg/kg dezocine was used. Primary outcome measures were Visual Analog Scale (VAS) score at 4 h, 8 h, 24 h and 48 h after surgery. The second outcome measures were Interleukin-6 (IL-6) and C-reactive protein (CRP) levels in the serum 10 minutes before anesthesia induction, and at 24 h and 48 h after surgery. Results The VAS scores at 4 h, 8 h, 24 h and 48 h after the surgery in the ES group vs DE group were 2.70 vs 3.50(P=0.013),2.35 vs 3.15(P=0.004),1.69 vs 2.58(P=0.002), and 1.50 vs 2.26(P=0.002), respectively. The serum IL-6 concentrations 10 minutes before anesthesia induction, and at 24 h and 48 h after surgery in the ES group and DE group were 34.39 and 34.12(P=0.901),112.33 and 129.60(P=0.014), and 89.69 and 108.46(P<0.001), respectively. The CRP levels in serum 10 minutes before anesthesia induction, and at 24 h and 48 h after the surgery in the ES group and DE group were 5.99 and 5.86(P=0.639), 28.80 and 35.37(P<0.001), and 23.17 and 30.11(P<0.001), respectively. Conclusion For postoperative pain after LC, 1.5mg/kg esketamine provided better analgesia and reduced inflammation levels than 0.3mg/kg dezocine. Trial registration This trial was registered in the China Clinical Research Information Center in 31/05/2023 : https://www.chictr.org.cn/bin/home (Registration number: ChiCTR2300072011).